EVALUASI KINERJA SIMPANG TIGA BERSINYAL (STUDI KASUS: SIMPANG JALAN TB SIMATUPANG – JALAN CONDET): EVALUASI KINERJA SIMPANG TIGA BERSINYAL (STUDI KASUS: SIMPANG JALAN TB SIMATUPANG – JALAN CONDET) - warianti, krisna; Windari, Aulia Choiri; Sari, Ribut Nawang (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
Simpang tiga Jl. condet – Jl. TB Simatupang is the main road connecting East Jakarta with South Jakarta. The existing condition at the signalized intersection is a commercial area that can cause vehicle congestion at certain hours (peak hour). The purpose of this study is to determine the performance condition of the signalized intersection of Jalan TB Simatupang – Jalan Condet and the appropriate handling according to the condition of the intersection. Data processing uses the Indonesia Road Capacity Manual method (MKJI, 1997). Data processing is carried out for 2 days in the morning, afternoon, and evening for 2 hours in each time period. The data was used to calculate the value of queue length, degree of saturation, signal cycle time, delay and Level of Service (LOS) at each arm of the intersection of Jalan TB Simatupang – Jalan Condet. The results of the analysis on the existing condition of the three-signal intersection are Level of Service in category F (very bad) during peak hours, with a cycle time of 153 seconds. An alternative solution was carried out to deal with this condition with the first alternative changing the cycle time to 100 seconds, the Level of Service value still shows F. For the second alternative with widening on each approach to 2.1 meters on the right side and 2.1 meters on the left side. Level of Service in category D (Less). Of the two alternatives, the second alternative is the best alternative to overcome the problems that occur at the signalized intersection of Jalan TB Simatupang – Jalan Condet.